Pelatihan teknik budidaya tanaman sayuran di lahan Tailing Mile Point 21 Timika: Training for the vegetable cultivation techniques in the Tailings Area of Mile Point 21 Timika - Saraswati Prabawardani; Sartji Taberima; Nouke L. Mawikere; Obaja Fenetiruma; Fiona D. N. Luhulima (IGKOJEI: Jurnal Pengabdian Masyarakat, 2023)
ABSTRACT  PT Freeport Indonesia has committed to restore tailings into fertile land through the reclamation and revegetation program. One of the revegetation activities is the cultivation of vegetable plants. In its implementation, field human resources are needed to be trained into capable field working people in vegetable cultivation. Thus, this training aims to provide guidance, and practice for field workers of PTFI Environmental Department Reclamation Division  in cultivating vegetable plants in the MP 21 Timika tailings land. The activity was carried out in June 2023. The method of this training was in the form of technical guidance given practically in the form of a plot demonstration in the field, which was preceded by a lecture. The activity was well attended by all participants. This activity consisted of land preparation, fertilization, seedling, sowing, and transferring the plants into the field. The result of the extension activity showed that the field workers who were trained became more skillful in cultivating vegetable plants, and also indicated by good growth of eggplant, tomato and chili.  Keywords: Cultivation; Revegetation; Tailings; Vegetables   ABSTRAK PT Freeport Indonesia telah berkomitmen untuk memberdayakan lahan tailing melalui kegiatan reklamasi dan revegetasi, diantaranya menjadi lahan budidaya. Salah satu kegiatan revegetasi adalah pembudidayaan tanaman sayuran, namun dalam pelaksanaanya dibutuhkan sumberdaya lapang yang mampu bekerja. Dengan demikian penyuluhan ini bertujuan untuk memberikan bimbingan dan praktek bagi tenaga lapang Divisi Reklamasi Departemen Lingkungan PTFI untuk membudidayakan tanaman sayuran di lahan tailing MP 21 Timika. Kegiatan dilaksanakan pada bulan Juni 2023. Metode kegiatan berupa bimbingan teknis yang diberikan secara praktis berupa demonstrasi plot di lapang yang didahului dengan bentuk ceramah. Kegiatan ini diikuti dengan baik oleh pekerja atau tenaga lapang PTFI dari sejak persiapan lahan, pemupukan, penyemaian, pembibitan, hingga penanaman di lapang. Hasil penyuluhan menunjukkan bahwa tenaga lapang yang dilatih menjadi lebih terampil dalam membudidayakan jenis tanaman sayuran, dan juga ditunjukkan oleh hasil pertumbuhan yang baik dari tanaman terong, tomat dan cabe. Kata kunci: Budidaya; Revegetasi; Sayuran; Tailing